PHATIC UTTERANCE ON MOVIE FLYING COLORS BY NOBUHIRO DOI - Yuniarsih; Eky Kusuma Hapsari; Andre Anugraha (WIDAI Japanese Journal, 2021)
The object of this thesis was phatic communication. The purpose of this study was aimed to know and reveal the shapes and fuction of the phatic utterance in communication that japanese is super phatic type of society. This thesis  was using  Nabuhiro Doi‘s Flying Colors as data source. This study was using descriptive qualitative as the method of analysis, and using documentation technique, notes and listening technique to  collect the data. Speech and SPEAKING are useful for knowing the utterance about whom, norms, purpose, etc in the communication. This thesis found that phatic utterance has seven shapes which are praise utterance, grateful utterance, appologize utterance, greeting utterance, encourage utterance, and small talk  utterance. This  thesis also  has  three  utterance function which are,  to  open communication, to break the silence and to close the communication.